Pelatihan Desain Website Sederhana Menggunakan WordPress untuk Siswa SMK 1 Parulian - Siregar, Kristian; Panjaitan, Muhammad Iqbal; Tamba, RL. Harmady; Siagian, Edward Robinson; Karo Karo, Siddik (CV. Devi Tara Innovations, 2025)
Website design skills are one of the important competencies needed in the digital era, especially for Vocational High School (SMK) students who are directed to be ready for work. This community service activity aims to improve the digital literacy and technical skills of SMK 1 Parulian students through training in creating a simple website using the WordPress platform. The implementation method includes preparation stages, direct training implementation, and evaluation in the form of pre-test and post-test. The results showed a significant increase in students' understanding of the concept and practice of website creation, as evidenced by the increase in post-test scores and students' success in creating a functional personal website. In addition, feedback from the questionnaire showed that participants felt enthusiastic and rated this training as very beneficial for their skill development. With this training, it is hoped that vocational school students will be able to develop their potential in the field of information technology, especially in WordPress-based digital content management.